BIOPROSPECTING SOIL ACTINOMYCETES: ISOLATION AND ANTIBACTERIAL ASSAY - Suhartono Suhartono; Risa Nursanty (Universitas Syiah Kuala, 2012)
Searching for novel bioactive compounds of microorganisms is increasing. Actinomycetes are a group of bacteria that have potential as a major producer of bioactive compounds. This study aimed to isolate and evaluate the isolates of actinomycetes collected from soil. This research was carried out in three stages, namely the field sampling, isolation of actinomycetes, screening the potential as a producer of bioactive compounds (antimicrobials). A total of 11 isolates of actinomycetes have been isolated in this study. The isolates varied in morphological characteristics. The antibacterial evaluation showed that nine isolates (81.8%) that were able to inhibit either the test organism. Three isolates of ACT-04, ACT-05, ACT-06 and ACT-11 were capable of inhibiting both bacterial targets.